Roni Horn: Inner Geography exhibition, The Baltimore Museum of Art, February 23 – April 17, 1994 - Baltimore Museum of Art (Archives and Manuscripts Collections, The Baltimore Museum of Art, 1994)
Since 1975 Roni Horn has made frequent solitary journeys to Iceland, and her experience of the island has profoundly influenced her work. Yet of the three primary arenas in which she works -- installations, drawings, and books -- only the book series, 'To Place' speaks directly about Iceland.